PENERAPAN MEDIA PEMBELAJARAN POWERPOINT UNTUK PENINGKATAN HASIL BELAJAR PEMBELAJARAN TEMATIK TEMA 3 SUBTEMA 1 PESERTA DIDIK KELAS V DI SDN 265 BANDUNGKULON - Siti Sholiha Nurfaidah; Sandi Nur Cahyatika Aditya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research aims to improve learning outcomes by using powerpoint learning media of class V students in SDN 265 Bandungkulon. This research is a class action research (PTK) that is qualitative descriptive by using a qualitative approach that is reinforced by a quantitative approach, by taking the background of SDN 265 Bandungkulon. The subject of this research is the students of class V/C SDN 265 Bandungkulon, while the object of this research is to improve the learning outcomes of learners by using powerpoint learning media on thematic learning of class V theme 1 Subtheme 3. This research was conducted in three cycles and through four stages. includes: planning, implementation, observation, and reflection. Data were obtained through observation, learning implementation, live tests and documentation. The results of this study show that the application of powerpoint learning media can improve the learning outcomes of learners. The improvement of learners' learning outcomes can be measured from the evaluation of cycle I, cycle II and cycle III. Seen the increase in learning outcomes of learners from cycle I to cycle III who have met the learning achievement, namely in cycle I by 41.37% (12 learners), in cycle II by 62.06% (18 learners) and in cycle III by 79.31%(23 learners). The results of research in SDN 265 Bandungkulon have been achieved well, that is, there is an increase in learners' learning outcomes with the application of powerpoint learning media.